Excellence in online journalism : exploring current practices in an evolving environment - Craig, David A. (Thousand Oaks, Calif. : SAGE, 2011)
Like the technologies that support it, the craft of online journalism is evolving quickly. Through interviews with more than 30 writers, editors, and producers and dozens of examples of strong work, this timely book shows students how to develop standards of excellence in their own work. The author uses a framework of ethical concepts to show how the field is evolving and challenged by competition, staffing limitations, and other pressures. Discussion is organized around four key elements: speed and accuracy with depth in breaking news; comprehensiveness in multimedia content; open-endedness in story development, including public contributions; and conversation with users. Chapter-length treatments of these topics bring home the realities of online work to students, who will appreciate how excellence and ethics online go hand in hand.
Includes bibliographical references and index.
Keywords: Online journalism